Blended learning compared to online learning in business, management, and accounting education: A bibliometric analysis and literature review - Santos, M. (Interdisciplinary and practical approaches to managerial education and training, 2022)
The journey of business, management, and accounting education over the past decades included several teaching methods which may nowadays be considered outdated for the modern students who live, learn, and connect through technology. This study clusters the academic literature addressing online learning and b-learning applied to educational and training in the business, management, and accounting. Through the collection of all the relevant publications in Scopus, this study uses automated text mining techniques in VOSviewer software for comparing the evolution overtime of the online and blended methods in the context of scientific knowledge production. The results unveil that online-learning-related literature is grouped in nine clusters, instead of the seven clusters in case of blended learning, meaning that the first is more disperse in terms of topics. An in-depth analysis of the studies most closely related to each cluster's terms allow the authors to provide critical reflections that help professionals when choosing the accurate method and also the academics in identifying future research agendas.